Reduction in case fatality rate from meningococcal disease associated with improved healthcare delivery. Issue 5 (1st November 2001) - Booy, R; Habibi, P; Nadel, S; de Munter, C; Britto, J; Morrison, A; Levin, M; Group, the Meningococcal Research
Abstract : BACKGROUND AND AIMS: The case fatality rate from meningococcal disease (MD) has remained relatively unchanged in the post antibiotic era, with 20–50% of patients who develop shock still dying. In 1992 a new paediatric intensive care unit (PICU) specialising in MD was opened. Educational information was disseminated to local hospitals, and a specialist transport service was established which delivered mobile intensive care. The influence of these changes on mortality of children with MD was investigated. METHODS: A total of 331 consecutive children with meningococcal disease admitted to the PICU between 1992 and 1997 were studied. Severity of the disease on admission was assessed using the paediatric risk of mortality (PRISM) score. Logistic regression analysis was used to correct for clinical severity, age, and sex; death was the outcome, and year of admission, a temporal trend variable, was the primary exposure. RESULTS: The case fatality rate fell year on year (from 23% in 1992/93 to 2% in 1997) despite disease severity remaining largely unchanged. After adjustment for age, sex, and disease severity, the overall estimate for improvement in the odds of death was 59% per year (odds ratio for the yearly trend 0.41). CONCLUSIONS: A significant improvement in outcome for children admitted with MD to a PICU has occurred in association with improvements in initial management of patients with MD at referring hospitals, use of a mobile intensive care service, and centralisation of care in a specialist unit.